Twenty years of Colombian experience with enzymatic screening in patients with features of mucopolysaccharidosis. Issue 5 (28th July 2022) - Uribe‐Ardila, Alfredo; Ramirez‐Borda, Johana; Ayala, Adis
Abstract: Mucopolysaccharidoses (MPSs) are a group of genetic alterations whose effect is the progressive intralysosomal accumulation of glycosaminoglycans. Affected individuals are deficient in one or more lysosomal enzymes which, depending on the MPS, may cause coarse facial features, short stature, multiple skeletal dysplasia, joint stiffness, or developmental delay. Their diagnosis is mostly performed late or incorrectly, and it represents a challenge since it requires specialized tests only performed in major cities. This makes it difficult for patients to have access to physicians since their geographical location is distant and therefore, the use of samples collected in solid‐phase represents an advantage for the study of high‐risk populations. In addition, epidemiological information about rare diseases, especially in Latin America, is scarce or inconsistent. Our aim was to report the experience of 20 years of selective screening by assessing enzyme activity and reporting incidence values of MPS in Colombia. This study validated a group of fluorometric endpoint techniques in 8239 patients. The samples were dried blood spots (DBS) collected on filter paper and leukocyte extracts. Reference values in the Colombian population for α‐l ‐iduronidase, iduronate 2‐sulfatase, α‐ N ‐acetylglucosaminidase, N ‐acetylglucosamine‐6‐sulfate sulfatase, β‐galactosidase, arylsulfatase B, and β‐glucuronidase were established in leukocyte extracts, and patients reference ranges were updated in the case of DBS samples. Incidence values were calculated for each MPS and the distribution of cases across the country is also shown. This study offers very useful information for the health system, the scientific community, and it facilitates the diagnosis of these disorders. This is indispensable when seeking to develop new diagnostic or treatment approaches for patients.